(untitled) (Global Journal of Human-Social Science, 2016)
Purpose The purpose of this study is to identify and describe the characteristics of literature published in the field of KM over the period of 8 years with a view to identify the place language year of publication subject areas forms of documents country of origin etc Design methodology approach A total numbers of 4371 items are collected from the source document Web of Science from the year 2007-2014 Findings The overall productivity of Knowledge Management KM works has been growing reaching up to 495 publications per year from 2007 to 2014 but their productivity are somewhat irregular Most of the literature of KM in Web of Science is published in non KM focal journals KM play a major role from the ancient time so there is differentiate in research by country wise The most productive top five countries in the field of KM research are USA England Taiwan Spain and China